2009
DOI: 10.4067/s0718-58392009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Root Growth of 'Thompson Seedless' Grapevines and Soil Temperature

Abstract: With the purpose of characterizing the growth of the root system of table grapes (Vitis vinifera L.) cv. Thompson Seedless and its relationship with soil temperature, research was carried out during the 2004-2005 growing season in vineyards in the Copiapó and Huasco Valleys. Four plants were chosen and rhizotrons were used to measure the growth of the root system. Measurements were performed once a week from September 2004 to September 2005, estimating the intensity of root growth and its annual distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
3
13
0
3
Order By: Relevance
“…The three peaks observed in R R 20 (Fig. 5b) closely match the pattern of new root intersections observed in a rhizotron study of V. vinifera cv Thompson seedless, undertaken in Chile by Callejas et al. (2009) under drier climatic conditions.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The three peaks observed in R R 20 (Fig. 5b) closely match the pattern of new root intersections observed in a rhizotron study of V. vinifera cv Thompson seedless, undertaken in Chile by Callejas et al. (2009) under drier climatic conditions.…”
Section: Discussionsupporting
confidence: 79%
“…The main R RF 20 peak in midsummer was much more pronounced than the peaks of root growth observed in the above‐mentioned studies in V. vinifera (Eissenstat et al. , 2006; Callejas et al. , 2009).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Root observation studies in grapevines have clearly indicated that root density (Daulta and Chauhan 1980;Southey and Archer 1988), root distribution (Bassoi et al, 2002;Morano and Kliewer 1994;Pradubsuk and Davenport 2011) and seasonal root growth dynamics (Bonomelli et al, 2012;Eissenstat et al, 2006;Mullins et al, 1992) are influenced by the soil environment (Callejas et al, 2009;Comas et al, 2010;Stevens and Douglas 1994), genotype (Swanepoel and Southey 1989) and aboveground phenology (Bonomelli et al, 2012). A significant number of studies have addressed root growth dynamics at weekly to seasonal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…así como los niveles productivos de los huertos, sobre todo en las condiciones de temperatura de suelo del desierto de Atacama (Callejas et al, 2009), cuando existe una adecuada disponibilidad hídrica. Callejas et al (2012) ratifican para vides lo señalado por Sellés et al (2003), en el sentido que desde el punto de vista de funcionalidad y actividad, las plantas que presentan una tendencia a ser más productivas poseen raí-ces de menor diámetro y de color blanco, dado que las raíces menores a 2 mm de diámetro son las más importantes en términos de la absorción de agua y nutrientes (Mullins et al, 1992).…”
Section: Distribución De Raícesunclassified